ANALISIS MARJIN PEMASARAN LADA PUTIH DALAM MENDUKUNG DAYA SAING PRODUK AGROINDUSTRI LADA INDONESIA - Muslim, Chairul; Nurasa, Tjetjep (Indonesian Journal of Socio Economics)
White pepper export from Indonesia is mainly in the form of raw products or unprocessed.Â  The objective of the study is to figure out marketing margin of white pepper marketing. The study employs marketing margin analysis.Â  The survey was carried out in Bangka and Belitung Province, production center of white pepper in Indonesia.Â  The study suggests that farmerâs share to final price of white pepper was equal to 77% or Rp 24.400 / kg. The highest marketing expenditure was borned by collector, i.e. around Rp 900/kgÂ  Price differentiation in line with quality was not responded by farmers, as there is no incentive in doing so.Â  The highest marketing margin was obtained by exporters, who have better access and information for international trade, as well as exchange rate fluctuation, i.e. equal to Rp 1.800/kg. It is important that the rejuvenation of smallholder pepper farming shall be carried out by government in order to improve quantity and quality of products hence able to compete internationally..